Experimental investigation of influencing factors on the long-term strength of sliding zones of the Loess-Hipparion laterite landslide - Yanbo ZHU; Zhenqian LIU; Wenjie LI; Shuaisheng MIAO; Hongfei LI; Hengxing LAN (Shuiwen dizhi gongcheng dizhi, 2022)
The Hipparion laterite with strong creep characteristics and obvious strength attenuation after deformation is widely distributed in northwest China. However, previous studies have paid little attention to the long-term strength attenuation of the Hipparion laterite. In order to investigate the time effect of strength of the Hipparion laterite, the creep test of samples under different influence factors is carried out. The long-term strength is calculated by using the isochronal curve method based on the creep curves, and the sensitivity of influencing factors to the long-term strength is analyzed. The results indicate that the Hipparion laterite has strong creep characteristics, which are affected by the density, moisture content of samples and confining pressure. The smaller the dry density, the higher the moisture content of the samples, and the smaller the confining pressure, the greater the deformation of the sample in the creep process. After creep deformation, the strength of the Hipparion laterite decreases obviously with a strength loss rate of 6.67%−34.58%, which varies with the influence factors. The sensitivity of the long-term strength attenuation of the Hipparion laterite is different with the change of the influencing factors. The long-term strength is the most sensitive to the change of water content, followed by the change of confining pressure, and is the lowest with the change of dry density. The change of the strength loss rate of the Hipparion laterite presents different rules. The smaller the dry density is, the higher the water content is, and the lower the confining pressure is, the greater the strength loss rate is. The change range of the long-term strength loss rate is the most sensitive to the change of confining pressure, followed by the change of water content, and the long-term strength loss rate is the lowest with the change of dry density.